Identification and characterization of nucleolin as a COUP-TFII coactivator of retinoic acid receptor β transcription in breast cancer cells. - Lacey M Litchfield; Krista A Riggs; Alyson M Hockenberry; Laura D Oliver; Katelyn G Barnhart; Jian Cai; William M Pierce; Margarita M Ivanova; Paula J Bates; Savitri N Appana; Susmita Datta; Piotr Kulesza; et al. (PLoS ONE, 2012)
The orphan nuclear receptor COUP-TFII plays an undefined role in breast cancer. Previously we reported lower COUP-TFII expression in tamoxifen/endocrine-resistant versus sensitive breast cancer cell lines. The identification of COUP-TFII-interacting proteins will help to elucidate its mechanism of action as a transcriptional regulator in breast cancer.FLAG-affinity purification and multidimensional protein identification technology (MudPIT) identified nucleolin among the proteins interacting with COUP-TFII in MCF-7 tamoxifen-sensitive breast cancer cells. Interaction of COUP-TFII and nucleolin was confirmed by coimmunoprecipitation of endogenous proteins in MCF-7 and T47D breast cancer cells. In vitro studies revealed that COUP-TFII interacts with the C-terminal arginine-glycine repeat (RGG) domain of nucleolin. Functional interaction between COUP-TFII and nucleolin was indicated by studies showing that siRNA knockdown of nucleolin and an oligonucleotide aptamer that targets nucleolin, AS1411, inhibited endogenous COUP-TFII-stimulated RARB2 expression in MCF-7 and T47D cells. Chromatin immunoprecipitation revealed COUP-TFII occupancy of the RARB2 promoter was increased by all-trans retinoic acid (atRA). RARβ2 regulated gene RRIG1 was increased by atRA and COUP-TFII transfection and inhibited by siCOUP-TFII. Immunohistochemical staining of breast tumor microarrays showed nuclear COUP-TFII and nucleolin staining was correlated in invasive ductal carcinomas. COUP-TFII staining correlated with ERα, SRC-1, AIB1, Pea3, MMP2, and phospho-Src and was reduced with increased tumor grade.Our data indicate that nucleolin plays a coregulatory role in transcriptional regulation of the tumor suppressor RARB2 by COUP-TFII.